2020
DOI: 10.3390/ma13133037
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Hybrid Nanomaterials Based on Star and Linear Polymers of N,N′-Dimethylaminoethyl Methacrylate with In Situ Produced Silver Nanoparticles

Abstract: Well-defined linear and multi-arm star polymer structures were used as the templates for in situ synthesis and stabilization of silver nanoparticles (AgNPs). This approach led to hybrid nanomaterials with high stability and antibacterial activity to both Gram-positive and Gram-negative bacterial strains. The ecologically friendly so called “green” synthesis of nanomaterials was performed through AgNPs preparation in the aqueous solutions of star and linear poly(N,N′-dimethylaminoethyl methacrylate)s (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The cationic PDMAEMA star and its linear analog were able to reduce silver ions and led to the formation of silver nanoparticles (AgNPs) without any additional reducing agent. The polymer acts simultaneously as a stabilizer of the formed nanoparticles [ 71 ]. The hybrid nanomaterial based on star PDMAEMA was more stable than AgNPs with linear PDMAEMA, which indicated that the star structures better prevented undesirable aggregation of silver nanoparticles in the solution.…”
Section: Polymer Nano- and Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…The cationic PDMAEMA star and its linear analog were able to reduce silver ions and led to the formation of silver nanoparticles (AgNPs) without any additional reducing agent. The polymer acts simultaneously as a stabilizer of the formed nanoparticles [ 71 ]. The hybrid nanomaterial based on star PDMAEMA was more stable than AgNPs with linear PDMAEMA, which indicated that the star structures better prevented undesirable aggregation of silver nanoparticles in the solution.…”
Section: Polymer Nano- and Microstructurementioning
confidence: 99%
“…The research was then extended to quaternized and nonquaternized star and linear polymers. All studied structures exhibited antibacterial activity against the tested bacterial strains, but the incorporation of AgNPs into polymer structures enhanced the bactericidal activity of such hybrids by several times [ 71 ].…”
Section: Polymer Nano- and Microstructurementioning
confidence: 99%
“…It has been studied for its utility in gene delivery, as a sensor, and a mediator for drug encapsulation and release [6][7][8][9][10][11][12][13]. This methacrylate polymer is usually polymerized into self-assembled moieties, brushes, dendrimers, and star-like forms [7,14,15]. It is also combined with common monomers such as styrene and polyethylene glycol to make for more flexible and expanded usage [10,11,16].…”
Section: Introductionmentioning
confidence: 99%
“…It is also combined with common monomers such as styrene and polyethylene glycol to make for more flexible and expanded usage [10,11,16]. This includes surface modifications as well as stand-alone structures [14,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high surface energy, the Ag nanoparticles are easy to be aggregated in colloidal solution and subsequently reduce the antimicrobial activity. To this case, many Ag-nanocomposites have been fabricated to improve the dispersity by immobilizing the Ag nanocrystals on nanocarriers or being encapsulated within the porous templates, respectively [ 13 ]. To extend the effectiveness, the incorporation of Ag nano-antibacterial agents into a protection matrix is also favorable to enhance the sustainability [ 14 ].…”
Section: Introductionmentioning
confidence: 99%